STRATEGI PEMBINAAN BELA NEGARA GENERASI MUDA DI ERA PROXY WAR DIGITAL - Gunnarto; Ade David Siregar (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
This research is based on the challenges faced by Indonesian youth in the Industry 4.0 era and the increasingly prominent threat of Proxy War. Proxy War is a form of non-traditional threat that leverages digital technology, with youth, as active users of technology, becoming its primary target. This threat is characterized by the rapid development of information technology, which facilitates the spread of disinformation and propaganda. The purpose of this study is to identify and develop strategies to foster national defense awareness among the younger generation to face the challenges of the Industry 4.0 era and the growing threat of Proxy War. This research uses a qualitative method with a descriptive-analytical approach. Data were collected through interviews, observations, and literature studies, then analyzed using interactive analysis techniques, including data reduction, data presentation, and conclusion drawing. The results of the study indicate that strategies to build national defense awareness need to integrate digital literacy and information technology as efforts to enhance the ability of youth to recognize and respond to Proxy War threats. Moreover, fostering national defense awareness through programs that are adaptive to technological advancements is key to strengthening the ideological resilience of the younger generation. In conclusion, technology-based strategies for fostering national defense awareness can improve youth readiness in addressing digital era challenges and Proxy War threats. This awareness-building must focus on developing digital literacy and a strong sense of nationalism among the younger generation.